Escherichia coli "TatExpress" strains super‐secrete human growth hormone into the bacterial periplasm by the Tat pathway. Issue 12 (6th October 2017) - Browning, Douglas F.; Richards, Kirsty L.; Peswani, Amber R.; Roobol, Jo; Busby, Stephen J.W.; Robinson, Colin
Abstract: Numerous high‐value proteins are secreted into the Escherichia coli periplasm by the General Secretory (Sec) pathway, but Sec‐based production chassis cannot handle many potential target proteins. The Tat pathway offers a promising alternative because it transports fully folded proteins; however, yields have been too low for commercial use. To facilitate Tat export, we have engineered the TatExpress series of super‐secreting strains by introducing the strong inducible bacterial promoter, ptac, upstream of the chromosomal tatABCD operon, to drive its expression in E. coli strains commonly used by industry (e.g., W3110 and BL21). This modification significantly improves the Tat‐dependent secretion of human growth hormone (hGH) into the bacterial periplasm, to the extent that secreted hGH is the dominant periplasmic protein after only 1 hr induction. TatExpress strains accumulate in excess of 30 mg L −1 periplasmic recombinant hGH, even in shake flask cultures. A second target protein, an scFv, is also shown to be exported at much higher rates in TatExpress strains. Abstract : The Tat translocon can be used to target recombinant biopharmaceuticals to the Escherichia coli periplasm. However, due to the low abundance of Tat components this system has limited capacity. Here we have engineered the TatExpress series of strains, which super‐secrete biopharmaceuticals (e.g. human growth hormone and scFvs) into the E. coli periplasm, making Tat‐mediated export an industrially relevant system.